The United Nations and the African Union in the prevention of war crimes, crimes against humanity and genocide in Africa: lessons from Rwanda - Fernandez, Lovell (University of Pretoria, 2006)
Thesis (LLM (Human Rights and Democratisation in Africa)) -- University of Pretoria, 2004.